Clinical presentation and treatment of catameinal pneumothorax and endometriosis-related pneumothorax. (2nd December 2018) - Fournel, Ludovic; Bobbio, Antonio; Robin, Edouard; Canny-Hamelin, Emelyne; Alifano, Marco; Regnard, Jean-François
ABSTRACT: Introduction : Catamenial pneumothorax (CP) is defined as a recurrent spontaneous pneumothorax occurring in females of reproductive age. In the 'perimenstrual period, ' it is still considered relatively rare although accounting for 20–35% of spontaneous pneumothoraces occurring in premenopausal women. It is the most frequent manifestation of thoracic endometriosis, which can also cause pneumothorax during the intermenstrual period (TER non-CP). Areas covered : In this article, we review and comment the clinical presentation, etiopathogenesis, diagnostic criteria, and therapeutic management of CP and TER non-CP. We particularly emphasize on the surgical optimal treatment and associated multidisciplinary care and follow-up. Electronic databases, mostly PubMed, were used for searching terms including 'catamenial pneumothorax' and 'thoracic endometriosis.' Expert commentary : Clinical presentation and imaging of CP and TER non-CP are often unspecific except for possible visualization of endometriosis foci or diaphragmatic lesions at computed tomography-scan or magnetic resonance imaging. Thus, we recommend careful interrogatory and intraoperative inspection for appropriate diagnosis and treatment of pneumothorax in women. Despite better awareness of surgical teams, CP and TER-non CP are still associated with high rates of postoperative recurrence (around 30%). We strongly advocate for a multidisciplinary management including early surgical and chemical pleurodesis, resection of all visible endometriosis-related lesions, hormonal blockade, and prolonged follow-up.